Pelatihan Laporan Keuangan UMKM pada Rumah BUMN Purwokerto - Faizal Rizky Yuttama; Alfizi Alfizi; Budi Widadi; Iin Dyah Indrawati (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
For the development of small and medium enterprises, accounting is one of the most important factors that entrepreneures should not forget. Simple bookkeeping in small and medium businesses is very important for the progress of one’s business. On of the reasons why MSMEs find it difficult to develop is the poor accounting system for MSMEs. This is because the government pays little attention to these issues and many MSMEs are still reluctant to consider complex issues such as accounting and financial management. They just think that the profit is enough for their business or MSMEs to function and develop. This training aims to improve capabilities in producing accountable financial report to micro, small and medium enterprise stakeholders. Micro, small and medium enterprise (MSMEs) have made a significant economic contribution to economic development, especially in developing countries. In this regard, we are trying to do community service by providing knowledge and training for micro, small and medium enterprises with the theme of community service, namely MSME Financial Report Training.